Inflammation and endothelial gene polymorphism are associated with ischemic stroke - Wanli Chen; Jie Li; Jintao Zhou; Xingyang Yi; Hong Chen (Frontiers in Neurology)
AimEvaluate the correlation between ischemic stroke and genetic variations related to inflammation and endothelial function.MethodsThis was a multicenter cross-sectional research conducted in southwestern China. Residents aged ≥40 years voluntarily join in the face-to-face survey in 8 communities. 2,377 participants were at high risk of stroke, of which 429 had a previous history of ischemic stroke. We selected the 429 ischemic stroke patients as the research subjects, and adopted a 1:1 matching method to select 429 healthy people with a 2-year age difference and the same gender and hypertension as the control group. We detected genotypes of 19 variants in 10 genes related to inflammation and endothelial function. Analyze gene–gene interaction through generalized multifactor dimensionality reduction (GMDR).ResultsAnalysis found no statistically significant differences in age, gender, hypertension, BMI, and smoking history between ischemic stroke patients and healthy control group. Compared with the healthy group, ischemic stroke group has a higher proportion of diabetes, heart disease, dyslipidemia, stroke family history, and a higher proportion of lack of exercise. HABP2 rs7923349, NOS2A rs8081248, HABP2 rs932650 were related to stroke in univariate analysis. GMDR analysis showed significant gene–gene interactions between HABP2 rs7923349, HABP2 rs932650. After adjusting for covariates, high-risk interaction genotypes between these two variants were independently associated with higher stroke risk (OR, 3.578, 95% CI: 2.618–4.890, p < 0.001).ConclusionThis study found that specific variations in genes related to inflammation and endothelial function are associated with ischemic stroke. The high-risk interactive genotypes among HABP2 rs7923349, HABP2 rs932650 distinctly increased the risk of ischemic stroke.